Vaccination with Recombinant Subolesin Antigens Provides Cross-Tick Species Protection in Bos indicus and Crossbred Cattle in Uganda - Paul D. Kasaija (Vaccines, 2020)
Cattle tick infestations and transmitted pathogens affect animal health, production and welfare with an impact on cattle industry in tropical and subtropical countries. Anti-tick vaccines constitute an effective and sustainable alternative to the traditional methods for the control of tick infestations. Subolesin (SUB)-based vaccines have shown efficacy for the control of multiple tick species, but several factors affect the development of new and more effective vaccines for the control of tick infestations. To address this challenge, herein we used a regional and host/tick species driven approach for vaccine design and implementation. The objective of the study was to develop SUB-based vaccines for the control of the most important tick species (Rhipicephalus appendiculatus, R. decoloratus and Amblyomma variegatum) affecting production of common cattle breeds (Bos indicus and B. indicus x B. taurus crossbred) in Uganda. In this way, we addressed the development of anti-tick vaccines as an intervention to prevent the economic losses caused by ticks and tick-borne diseases in the cattle industry in Uganda. The results showed the possibility of using SUB antigens for the control of multiple tick species in B. indicus and crossbred cattle and suggested the use of R. appendiculatus SUB to continue research on vaccine design and formulation for the control of cattle ticks in Uganda. Future directions would include quantum vaccinology approaches based on the characterization of the SUB protective epitopes, modeling of the vaccine E under Ugandan ecological and epidemiological conditions and optimization of vaccine formulation including the possibility of oral administration.